2008
DOI: 10.1007/s11883-008-0017-z
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol consumption and heart failure: A systematic review

Abstract: Heart failure (HF) remains a major public health issue. It is estimated that about 500,000 Americans per year are diagnosed with HF. Despite advanced medical and surgical treatments for HF, mortality after the onset of HF is still high, thereby underscoring the importance of primary prevention. Among modifiable lifestyle factors, alcohol consumption appears to play a role in the development of HF. Although excessive drinking has been known to lead to alcoholic cardiomyopathy and light-tomoderate drinking may c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
77
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(82 citation statements)
references
References 48 publications
4
77
0
1
Order By: Relevance
“…A number of theories have been put forward for the onset and development of alcoholic complications, including oxidative damage, deposition of triglycerides, altered fatty acid extraction, decreased myofilament Ca 2+ sensitivity, impaired protein metabolism, and mitochondrial anomalies [193][194][195][196][197][198][199] . Not surprisingly, oxidative stress and mitochondrial damage have been shown to contribute to the toxic effects of alcoholic liver and myocardial injuries [200][201][202] .…”
Section: Alcohol Oxidative Stress and Mitochondrial Dysfunctionmentioning
confidence: 99%
“…A number of theories have been put forward for the onset and development of alcoholic complications, including oxidative damage, deposition of triglycerides, altered fatty acid extraction, decreased myofilament Ca 2+ sensitivity, impaired protein metabolism, and mitochondrial anomalies [193][194][195][196][197][198][199] . Not surprisingly, oxidative stress and mitochondrial damage have been shown to contribute to the toxic effects of alcoholic liver and myocardial injuries [200][201][202] .…”
Section: Alcohol Oxidative Stress and Mitochondrial Dysfunctionmentioning
confidence: 99%
“…Moderate alcohol consumption is associated with hypertension [47] and higher doses result in an increased risk of MI and stroke [48,49]. According to Saremi and Arora, [50] there is an increased risk of hypertriglyceridemia, cardiomyopathy, hypertension, and stroke if 3 or more standard drinks of alcohol are taken per day.…”
Section: Alcoholismmentioning
confidence: 99%
“…29 Genetic factors can determine how well alcohol is metabolized and can play a role in determining the interactions between alcohol and its metabolites and the heart. 30 For example, polymorphism of the alcohol dehydrogenase type 3 (ADH3) gene alters the rate of alcohol metabolism. It has been shown that moderate drinkers who are homozygous for the slow-oxidizing ADH3 allele have higher HDL levels and a decreased risk of myocardial infarction.…”
Section: Etiology and Pathophysiologymentioning
confidence: 99%